Poblar el desierto argentino. Modelos de civilización en la novela de la Organización Nacional - Eugenia Ortiz Gambetta (Nuevo mundo - Mundos Nuevos, 2012)
The thesis analyzes some cultural models in a corpus of argentine romances published between 1850 and 1880. In the first place, these paradigms are identified with some english personages that were shown in some sentimental and historical novels as examples of sociability, hard work and citinzenship. But on the other side, two groups were presented as anti-models : the aborigines and the gauchos. The validity or invalidity of such paradigms is presented here through the topic of the crossbreeding. In the second place, these models of civilization are studied in their relation to the space transformation. The argentine territory was considered, in the imaginatory of the XIXth century, as a desert in which the european immigrants had to make a transformation and had to fill its emptiness with their own descendence. The desert, in this way, was represented as an idyllic place (topofesía) or as a place more closely related to the real one (topography), but always as an agrestic space that has to be civilizated.All these models had as a background a dicothomy between civilization and barbarism, and they are closely linked with the progressist thinking of those years and with the romantic aesthetic. The analisys of these works has been made interweaving some canonical lectures with some historical and also polical essays.